Formulación de un modelo de gestión organizacional por procesos con el enfoque del Balanced Scorecard para la cooperativa de ahorro y crédito Imbacoop Cia.Ltda.de la ciudad de Otavalo. - Suarez Navarrete, Carla Elizabeth (2014)
The saving and credit IMBACOOP cooperative is located in the parish of San Pablo de Lago in Otavalo. Of the summary made to the cooperative system is determined that the saving and credit cooperatives are organizations built by natural and legal people that voluntarily join with the purpose to carry out activities of financial intermediation, previous the Superintendence de Economic Popular y Solidary authorization. Of the internal and external analysis of IMBACOOP cooperative states that the Institution does not have an organizational system by processes as an innovative tool that the cooperatives must apply, in the same way is not applied the Balanced Scorecard in the financial planning and evaluation. The organizational model by processes with the approach of the Balanced Scorecard will be an important tool in the organizational and financial management through the joint of macro processes and structured sub processes so that it has sequential activities that allow the planning, execution, measurement and analysis of the indicator of administrative management, financial to ensure the effectiveness and efficiency of the institutional management